Immunological Pathways Triggered by Porphyromonas gingivalis and Fusobacterium nucleatum: Therapeutic Possibilities? - de Andrade, Kívia Queiroz (Mediators Inflamm, 2019)
Porphyromonas gingivalis (P. gingivalis) and Fusobacterium nucleatum (F. nucleatum) are Gram-negative anaerobic bacteria possessing several virulence factors that make them potential pathogens associated with periodontal disease. Periodontal diseases are chronic inflammatory diseases of the oral cavity, including gingivitis and periodontitis. Periodontitis can lead to tooth loss and is considered one of the most prevalent diseases worldwide. P. gingivalis and F. nucleatum possess virulence factors that allow them to survive in hostile environments by selectively modulating the host's immune-inflammatory response, thereby creating major challenges to host cell survival. Studies have demonstrated that bacterial infection and the host immune responses are involved in the induction of periodontitis. The NLRP3 inflammasome and its effector molecules (IL-1β and caspase-1) play roles in the development of periodontitis. We and others have reported that the purinergic P2X7 receptor plays a role in the modulation of periodontal disease and intracellular pathogen control. Caspase-4/5 (in humans) and caspase-11 (in mice) are important effectors for combating bacterial pathogens via mediation of cell death and IL-1β release. The exact molecular events of the host's response to these bacteria are not fully understood. Here, we review innate and adaptive immune responses induced by P. gingivalis and F. nucleatum infections and discuss the possibility of manipulations of the immune response as therapeutic strategies. Given the global burden of periodontitis, it is important to develop therapeutic targets for the prophylaxis of periodontopathogen infections.